Bitter and sweet : food, meaning, and modernity in rural China - Oxfeld, Ellen, 1953- (California studies in food and culture ;, 2017)
"Less than a half century ago, China experienced a cataclysmic famine, which was particularly devastating in the countryside. For older people in rural areas, food now symbolizes everything from misery and extreme want to relative abundance. Young people, on the other hand, have a different relationship to food. Many young rural Chinese are migrating to rapidly industrializing cities for work, happy to leave behind the backbreaking labor associated with peasant agriculture. Bitter and Sweet examines the role of food in one rural Chinese community, as it has shaped everyday lives over the course of several tumultuous decades. In her superb ethnographic accounts, Ellen Oxfeld compels us to reexamine some of the dominant frameworks that have permeated recent scholarship on contemporary China, work that describes increasing dislocation and individualism and a lack of moral centeredness. By using food as our lens, we see a more complex picture, one in which connectedness and sense of place continue to play an important role, even in the context of rapid change."--Provided by publisher